Padrão de atividade e uso de habitat por Irara (Eira barbara, Linnaeus 1978) em áreas de altitude na Serra da Mantiqueira, Mata Atlântica, MG - Lima, Karen Cristina Braga (2018)
The activity pattern and habitat use of a species are important for understanding the natural history of the species and its ecology. Some species of carnivores are common, but little studied, as is the case of tayra (Eira barbara). The objective was to evaluate their activity pattern and the environmental factors that influence the frequency of occurrence of tayra in two ecosystems of the Serra da Mantiqueira, Atlantic Forest. The hypotheses are: areas with high altitudes had a negative influence on their presence; areas with a higher percentage of forests had a positive influence on their occurrence; the proximity of human constructions and highways influence negatively in its presence; in pach of tropical rain forest (FOD), the iraras will present diurnal habits, whereas in a Seasonal Semideciduous Montane Forest pach (FESM) they will present alterations in the activity pattern. Sampling was carried out in Parque Nacional do Itatiaia and in the Reserva Particular do Patrimônio Natural do Alto Montana, mountainous areas that extend from 600 to 2791 m of altitude. We conducted the study between October 2013 and October 2016 along 32 sampling points, 13 located in FOD and 19 in the FESM. At each point, we installed a camera-trap totaling a total sample effort of 35,040 camera/night and collected environmental variables. We collect as habitat measure in each sampling unit. To evaluate the activity pattern the tayra throughout the daily cycle, we performed the Rao’s spacing test(U). To evaluate the factors influencing the frequency of occurrence, we performed generalized linear models and model selection, by AICc. We obtained 189 independent records of tayras, 59 in FOD and 139 in FESM. The activity pattern was not uniformely distributed throughout the 24 hours and activity of the tayra was concentrated in the diurnal period, totaling 163 records. The peak of tayra activity was at eleven o'clock, in the FOD the peak was more concentrated and in the FESM the records were more dispersed. The frequency of records of the tayra decreased with the increase of the altitude and with an approximation of human constructions. Along an altitudinal gradient there were reductions in temperature and productivity as well as changes in vegetation. These changes can explain the lesser use of areas of higher altitude by tayra. The information obtained in this work can contribute to studies of predictions of climate change and conservation.